A High-Throughput Screening Assay for Determining Cellular Levels of Total Tau Protein - J. Dehdashti, Seameen; Zheng, Wei; R. Gever, Joel; Wilhelm, Robert; Nguyen, Dac-Trung; Sittampalam, Gurusingham; C. McKew, John; P. Austin, Christopher; B. Prusiner, Stanley (Current Alzheimer Research, 2013)
The microtubule-associated protein (MAP) tau has been implicated in the pathology of numerous neurodegenerative diseases. In the past decade, the hyperphosphorylated and aggregated states of tau protein have been important targets in the drug discovery field for the potential treatment of Alzheimer’s disease. Although several compounds have been reported to reduce the hyperphosphorylated state of tau or impact the stabilization of tau, their therapeutic activities are remain to be validated. Recently, reduction of total cellular tau protein has emerged as an alternate intervention point for drug development and a potential treatment of tauopathies. We have developed and optimized homogenous assays, using the AlphaLISA and HTRF assay technologies, for the quantification of total cellular tau protein levels in the SH-SY5Y neuroblastoma cell line. The signal-to-basal ratios were 375 and 5.3, and the Z’ factors were 0.67 and 0.60 for the AlphaLISA and HTRF tau assays, respectively. The clear advantages of these homogeneous tau assays over conventional total tau assays, such as ELISA and Western blot, are the elimination of plate wash steps and miniaturization of the assay into 1536-well plate format for the ultra–high-throughput screening of large compound libraries.
Keywords: tau protein